2011
DOI: 10.1007/s10750-011-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients in macroalgal biodiversity in the Southwest Atlantic between 36 and 55°S

Abstract: Different groups of marine benthic organisms show contrasting latitudinal patterns of biodiversity. The widely accepted paradigm of increasing biodiversity towards the tropics does not seem to be valid for macroalgal floras of the Southern Hemisphere. We compiled a database summarizing the distributional ranges of macroalgae along the coast of Argentina to test whether biodiversity decreases towards lower latitudes, as in the Pacific coast of South America, and whether breaking points in the geographical distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
4
22
0
2
Order By: Relevance
“…The proportion of the three groups follows the trend observed by Liuzzi et al (2011) and by Miloslavich et al (2011) for the Argentinean coast. The total number of Rhodophyta, Chlorophyta and Phaeophyceae taxa found in the three sites represented an 11%, 22% and 20% of the total species of each group registered for the Patagonian shelf subregion of South America (Miloslavich et al 2011).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The proportion of the three groups follows the trend observed by Liuzzi et al (2011) and by Miloslavich et al (2011) for the Argentinean coast. The total number of Rhodophyta, Chlorophyta and Phaeophyceae taxa found in the three sites represented an 11%, 22% and 20% of the total species of each group registered for the Patagonian shelf subregion of South America (Miloslavich et al 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Recent biogeographic studies along the Argentine coast have demonstrated that most of the seaweed studies were conducted at high latitudes (Liuzzi et al 2011;Wieters et al 2012), mainly in the provinces of Chubut, Santa Cruz and Tierra del Fuego (Mendoza 1999;Asensi and Küpper 2012;Boraso 2013). According to these studies the floristic information about the coasts located in latitudes lower than 42° S is sparse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis showed areas of disjunction (sets 5, 6, 13, 14, Figure 1, and set 5, Figure 2) in the SWAO, in contrast with inshore/offshore areas and latitudinal gradients of biodiversity already documented for the marine realm in biogeographic studies (e.g., Searless 1984; Calder 1992; Liuzzi et al 2011;Fautin et al 2013). Areas of disjunction, recognized by EA, are common in nature (Casagranda et al 2012), and can be related to several ecological and historical aspects of the SWAO.…”
Section: Discussionsupporting
confidence: 46%